An assessment of liquidity risk among listed commercial banks in Ghana - Antwi, Nana Agyeman Prempeh (2016)
A Thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Business Administration (Finance Option)